Facilitating English Language teaching through AI- based drama in Palestine - Bsharat, Tahani; Sheikh Ahmad, Ismail (IGI Global Scientific Publishing, 2025)
Artificial Intelligence (AI) has the potential to significantly reshape the landscape of education through the integration of AI- powered tools, personalized learning algorithms, and virtual and augmented reality. In a study exploring the integration of AI- based drama in English language teaching in Palestine, a cohort of 43 teachers from both governmental and private schools participated in a questionnaire- based assessment. The survey sought to capture their perspectives on AI, AI- based drama techniques, the impact of AI in EFL classrooms, and the challenges associated with its implementation. Utilizing SPSS (V. 23), descriptive statistics, independent sample t- tests, and ANOVA tests were employed to analyze the data. The findings revealed a prevailing optimism among the participating educators, indicating their confidence in the potential of AI to enhance the EFL teaching and learning experience. Furthermore, the teachers identified financial and technical hurdles as the primary challenges. The findings underscore the imperative for comprehensive teacher training programs focused on effectively integrating AI tools in EFL education.